Mapping the Landscape of Corpus-based Pedagogy in English Education: Global vs. Indonesian Researcher Perspectives - Yulia Agustina; M. Adib Nazri; Budi Setiawan (Journal of Educational Studies, 2025)
Corpus linguistics has emerged as a powerful framework for analyzing authentic language use, shaping both theoretical and applied linguistics. Grounded in Rogers’ Diffusion of Innovations Theory (Rogers, 2003)[1], this study views corpus-based pedagogy as an educational innovation whose adoption varies across contexts. While globally corpus research has gained momentum in English language teaching and teacher training, its application in Indonesia remains modest and underexplored. This study aims to map the publication trends, thematic clusters, and collaboration networks in corpus-based educational research from both global and Indonesian perspectives using a bibliometric approach. It employed a bibliometric research design using the Scopus database to map publication trends, thematic clusters, and collaboration networks in corpus-based educational research. Data covering 1990-2024 were analyzed through VOS viewer, focusing on co-authorship, co-citation, and keyword co-occurrence to identify global trajectories and Indonesian contributions. The analysis of 810 publications revealed rapid global growth after 2010, with peaks in 2023, particularly in areas such as vocabulary acquisition, grammar instruction, and discourse analysis. Corpus linguistics remains the central theme, branching into sub-fields like data-driven learning (DDL), academic writing, and second language acquisition. In contrast, Indonesian contributions were limited to four Scopus-indexed articles up to 2025, largely descriptive and with minimal pedagogical focus. Corpus-based research has become central in global applied linguistics but is still at an early adoption stage in Indonesia. The disparity highlights infrastructural, awareness, and visibility gaps. Stronger institutional support, integration into teacher education, and classroom-based research are essential for Indonesia to align with global trends.